Photocatalyst composites of luminescent trinuclear copper(I) pyrazolate complexes/titanium oxide for degradation of 2,4-dichlorophenoxyacetic acid - Lintang, H. O. (Trans Tech Publications Ltd, 2016)
Here phosphorescent trinuclear copper(I) pyrazolate complexes ([Cu3Pz3]), synthesized from 3,5-dimethyl and 4-(3,5-dimethoxybenzyl)-3,5-dimethyl pyrazole ligands for complexes [Cu3Pz3]1 and [Cu3Pz3]2, were successfully impregnated into TiO2 with concentration of 0.1 mol%. These luminescent photocatalyst composites ([Cu3Pz3]1 or 2/TiO2) gave 60% and 49% of dichlorophenoxyacetic acid (2,4-D) degradation after 1 h for [Cu3Pz3]1/TiO2 and [Cu3Pz3]2/TiO2, while TiO2 only showed 48%. The higher activity observed on [Cu3Pz3]1/TiO2 than the TiO2 would come from the efficient reduction of electron-hole recombination, while less dispersion of complex [Cu3Pz3]2 with more rigid structure compared to complex [Cu3Pz3]1 gave similar activity of the [Cu3Pz3]2/TiO2 to the TiO2.